ANALISIS KEINDAHAN BAHASA TERHADAP PEMAHAMAN MUKJIZAT AL-QUR'AN DALAM SURAH AL-'ALAQ (ANALISIS STILISTIKA SURAH AL-'ALAQ AYAT 1-5) - Muhammad Aminuddin Jamal (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The beauty of language in the Qur'an plays a crucial role in conveying divine messages. The style of language used in the Qur'an not only touches on aesthetic aspects but also strengthens the understanding of the meaning contained therein. In the context of Surah al-'Alaq verses 1-5, the beauty of language can be seen through various elements such as rhyme, metaphor, and precise and profound word choice. However, although the beauty of the language of the Qur'an has been widely discussed, research that focuses on the direct influence of this beauty on the understanding of miracles is still relatively lacking. Most studies focus more on theological or historical aspects without deeply exploring the relationship between aesthetic aspects and understanding of meaning. Therefore, this study aims to analyze the influence of the beauty of language on the understanding of the miracles of the Qur'an with a case study on Surah al-'Alaq verses 1-5 through a stylistic approach. The approach used in this study is a qualitative approach with a stylistic analysis method. This type of research is descriptive analysis and literature study. The data in this study is the text of Surah al-'Alaq verses 1-5 of the Qur'an. The main data source is the Arabic manuscript of the Qur'an. In addition, additional data sources include commentaries on the Qur'an, books on the stylistics of the Qur'an, scientific articles, and other literature that discuss aspects of the beauty of language and the miracles of the Qur'an. In this study, several stylistic theories are used to analyze the elements of the beauty of language in Surah al-'Alaq verses 1-5. The stylistic theory by Geoffrey Leech is the main basis. The Beauty of Language in the Qur'an According to Muhammad Abdel Haleem, a professor of Islamic Studies at SOAS, University of London, the beauty of the language of the Qur'an plays an important role in conveying moral and spiritual messages. Understanding the Miracles of the Qur'an, Yusuf al-Qaradawi, a famous scholar from Egypt, emphasized that the miracle of the Qur'an lies in its ability to answer various intellectual and moral challenges throughout the ages. The results show that the beauty of language in Surah al-'Alaq verses 1-5 has significant implications both theoretically and practically for the study of the miracles of the Qur'an. With a deeper understanding of the linguistic and rhetorical aspects of the Qur'an, it is hoped that Muslims can better appreciate the miracles of the Qur'an and apply the values contained therein in their daily lives. Hopefully, this research can be a valuable contribution to the study of the Qur'an and provide inspiration for further research in the future.